A review of wild boar Sus scrofa diet and factors affecting food selection in native and introduced ranges - Barrios Garcia Moar, Maria Noelia (2014)
1. The wild boar Sus scrofa is an omnivore with one of the largest geographical ranges of all species. However, no synthesis exists on its diet, feeding behaviour and factors affecting food selection in its native and introduced ranges. 2. A literature review and a test of effect size revealed significant differences in wild boar diet composition in native and introduced ranges. Wild boar diet is dominated by plant material (∼90%) in both ranges, but animal matter and fungi are consumed in greater proportions in the introduced range than in the native range. Food items frequently include agricultural crops (especially in the native range) and endangered animal species (especially in the introduced range). Energy requirements, food availability, and seasonal and geographical variations are major factors influencing food selection by wild boar. These factors may also interact with human activities (e.g. agricultural crops, supplementary feeding) to influence diet composition further. 3. Dietary studies should be more rigorous and consistent across ranges to allow better comparisons. A detailed study of diet in combination with seasonal patterns of habitat use could provide key information such as target species and susceptible habitats on which management efforts should focus.